Crusades : medieval worlds in conflict - International Symposium on Crusade Studies (1st : 2006 : Saint Louis, Mo.); Madden, Thomas F.; Naus, James L.; Ryan, Vincent (Farnham, Surrey, England ; Burlington, VT : Ashgate Pub. Co.)
PSZJBL